Addition and recombination of Mycovellosiella species - A.K. SARBHOY, KIRTI BHALLA and (Indian Phytopathology, 2002)
Mycovellosiella adinicola sp. nov. occurring on Adina cordifolia is described and illustrated. Mycovellosiella fulvum on Lycopersicon esculentum, M. lantanae var. cubensis on Lantana camara and M. sacchari on Saccharum officinarum are recombined toCladosporium fulvum [Fulvia fulva] comb. nov., C. lantanae comb. nov. and Pseudocercospora sacchari comb. nov.